Seed quality of Hyacinth beans (Lablab purpureus L.) influenced by drying methods and storage temperatures - Mohd Yahaya, Aliyah (2020)
Lablab purpureus or known as Hyacinth bean is a high-value legume that has potential as an important vegetable crop due to its dietary value which is high in protein content. It also has anti-cancer properties but the crop has remained unexploited. To promote the cultivation of this legume good quality seeds would be a prerequisite. Apart from the field related production factors, problems that often occur in seed production are the post-harvest handling which includes drying and storage. Therefore, this study was conducted to determine suitable drying method and storage temperature for Hyacinth bean seed. Seeds were harvested at 30 days after anthesis (DAA) and subjected to different drying methods namely sun, shade, oven (35±2°C) and drying beads to obtain target moisture content (14, 12, 10%). The experiment adopted the Completely Randomized Design (CRD) with three replicates. Dried samples were taken randomly for seed physical characteristics, moisture content and germination. Results showed that, Hyacinth bean seeds dried using oven and drying beads attained 10% moisture content within 24 hours while those dried under the sun and shade required up to 72 hours to reach 10% MC. The most rapid rate of drying was by using drying beads and seeds dried with drying beads recorded the highest germination percentage (71%) and had high seed vigour index (20.46). Both shade and drying beads gave good results with drying beads being more economical for adoption by farmers. In contrast, sun and oven drying had large number of dead seeds. Bead- dried seeds were then stored at two storage temperature which are ambient (27.7-34.2°C; 74±5% RH) and fridge (2.0-5.0°C; 25±5% RH) for six months. Experiment was arranged in CRD with three replicates. The results revealed that after six months of storage, seeds stored under refrigerated temperature at ≤5.0℃ recorded higher germination (≥70%) compared with (≤ 50%) in ambient temperature. Seed vigour index was also higher (17.49) when stored under refrigerated temperature compared to ambient (8.67). In addition, under ambient declining in antioxidant enzymes activities, germination performance and seedling growth were recorded after six months of storage. Therefore, it is best stored refrigerated ( ≤ 5℃ ) in order to retain storability. It is concluded that Hyacinth seeds were best to bead-dried to 10% MC and further stored under refrigerated temperature in which the germination and defence mechanism of the Hyacinth were maintained.